Structural studies of metastable and equilibrium vortex lattice domains in MgB2. (4th June 2019) - Louden, E R; Leishman, A W D; Rastovski, C; Kuhn, S J; DeBeer-Schmitt, L; Dewhurst, C D; Zhigadlo, N D; Eskildsen, M R
Abstract: The vortex lattice (VL) in MgB2 is characterized by the presence of long-lived metastable states (MSs), which arise from cooling or heating across the equilibrium phase boundaries. A return to the equilibrium configuration can be achieved by inducing vortex motion. Here we report on small-angle neutron scattering studies of MgB2, focusing on the structural properties of the VL as it is gradually driven from metastable to equilibrium states (ESs) by an AC magnetic field. Measurements were performed using initial MSs obtained either by cooling or heating across the equilibrium phase transition. In all cases, the longitudinal correlation length remains constant and comparable to the sample thickness. Correspondingly, the VL may be considered as a system of straight rods, where the formation and growth of ES domains only occurs in the two-dimensional plane perpendicular to the applied field direction. Spatially resolved raster scans of the sample were performed with apertures as small as 80 μ m, corresponding to only 1.2 × 10 6 vortices for an applied field of 0.5 T. These revealed spatial variations in the metastable and equilibrium VL populations, but individual domains were not directly resolved. A statistical analysis of the data indicates an upper limit on the average domain size of approximately 50 μ m.